2018
DOI: 10.1111/bcpt.13038
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal and Systemic Responses of Obese TypeIIDiabetic Rats to Chronic Exposure to a Hyperbranched Polyglycerol‐Based Dialysis Solution

Abstract: Metabolic syndrome (MetS) is commonly observed among peritoneal dialysis (PD) patients, and hyperbranched polyglycerol (HPG) is a promising glucose-sparing osmotic agent for PD. However, the biocompatibility of a HPG-based PD solution (HPG) in subjects with MetS has not been investigated. This study compared the local and systemic effects of a HPG solution with conventional physioneal (PYS) and icodextrin (ICO) PD solutions in rats with MetS. Obese type 2 diabetic ZSF1 rats received a daily intraperitoneal inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…HPG (1 kDa) was synthesized as described previously [11, 12]. A hypertonic HPG PD solution (denoted as HPG here, approximately 402 mOsmol/kg, pH 7.4) was prepared by dissolving HPG (1 kDa, 6% w/v) in a buffered electrolye solution that had the same composition as that of PYS without glucose: sodium chloride (538 mg/100 mL), sodium lactate (168 mg/100 mL), calcium chloride dehydrate (18.4 mg/100 mL), magnesium chloride hexahydrate (5.1 mg/100 mL) and sodium bicarbonate (210 mg/100 mL) [11, 13, 14]. PYS (2.27% glucose, 395 mOsmol/L, pH 7.4) was purchased from Baxter Healthcare Co. (Deerfield, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPG (1 kDa) was synthesized as described previously [11, 12]. A hypertonic HPG PD solution (denoted as HPG here, approximately 402 mOsmol/kg, pH 7.4) was prepared by dissolving HPG (1 kDa, 6% w/v) in a buffered electrolye solution that had the same composition as that of PYS without glucose: sodium chloride (538 mg/100 mL), sodium lactate (168 mg/100 mL), calcium chloride dehydrate (18.4 mg/100 mL), magnesium chloride hexahydrate (5.1 mg/100 mL) and sodium bicarbonate (210 mg/100 mL) [11, 13, 14]. PYS (2.27% glucose, 395 mOsmol/L, pH 7.4) was purchased from Baxter Healthcare Co. (Deerfield, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In a rat model of acute PD, HPG-based PD solutions produce similar or better fluid and waste removal while preserving the PM function compared to either Dianeal (2.5% glucose) or Physioneal (PYS) (2.27% glucose) [11, 12]. Very recently, we have also demonstrated that HPG is superior to glucose for long-term preservation of the PM in a rat model of chronic PD [13, 14]. All these preclinical studies may suggest that HPG is a promising alternative to glucose in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in a rat model of acute (4 h) or chronic (3 months) PD have shown hyperbranched polyglycerol-containing PD fluid, as compared to glucose-based PD solutions, may induce less peritoneal injury and inflammation while achieving similar ultrafiltration and waste removal [60,61]. A more recent study [62] compared hyperbranched polyglycerol fluid to low-GDP and icodextrin PD fluid in a rat model (obese type 2 diabetic ZSF1 rats) of metabolic syndrome. At the end of the 3 months treatment period, the authors found that PD fluid containing hyperbranched polyglycerol better preserved the structures and function of the peritoneal membrane and kidneys, and induced less systemic adverse effects on metabolism, immune response and serum antioxidant capacity [62].…”
Section: Pd Solutions Under Developmentmentioning
confidence: 99%
“…A more recent study [62] compared hyperbranched polyglycerol fluid to low-GDP and icodextrin PD fluid in a rat model (obese type 2 diabetic ZSF1 rats) of metabolic syndrome. At the end of the 3 months treatment period, the authors found that PD fluid containing hyperbranched polyglycerol better preserved the structures and function of the peritoneal membrane and kidneys, and induced less systemic adverse effects on metabolism, immune response and serum antioxidant capacity [62]. However, caution must be taken when evaluating studies with icodextrin performed in rats.…”
Section: Pd Solutions Under Developmentmentioning
confidence: 99%
“…Hyperbranched polyglycerol containing PD fluid achieved similar solute and water transport rates in rats and induced less peritoneal membrane damage (Mendelson et al., 2013; Du et al., 2016), but data on the metabolism of polyglycerol in plasma and ramifications of plasma accumulation and tissue disposition with long-term use are scant. A recent study in obese type 2 diabetic ZSF1 rats over 3 months suggests less systemic adverse effects on the kidneys and the plasma oxidative status with hyperbranched polyglycerol fluid as compared to second-generation and icodextrin PD fluid (La Han et al., 2018).…”
Section: Novel Pd Fluid Prototypesmentioning
confidence: 99%